Amalgamation of high-κ dielectrics with graphene: A catalyst in the orbit of nanoelectronics and material sciences - Sadhak Khanna; Sadhak Khanna; Sadhak Khanna (Frontiers in Physics, 2022)
In electronics, the size of transistors has been reduced to a few nanometers. Electronic devices’ accuracy and authenticity face a major problem of leakage current. To solve this tricky situation, high-κ dielectrics which have a huge band gap and permittivity are established to increase the capacitance and remove the leakage current. Three major properties are related to current flow: 1) band gap, 2) resistance, and 3) dielectric constant. High-κ or higher dielectric constant shows how much charge a material can hold. A large band gap is needed to vanquish charge injection that causes leakage current. So, these are the insulating materials that store charges when placed in between metallic plates. The dielectric thickness of high-κ can be enhanced without enhancing the capacitance, hence reducing the leakage current. These materials need to be functionalized. Materials with low physical and chemical barriers need to be functionalized with them. The best material to be integrated with these high-κ dielectrics is graphene, as the goal of large area uniformity of electrical properties is achievable with this and easily separable graphene is also available. Here, we will scrutinize the current advancement in graphene electronics-based research on high-κ dielectrics such as Al₂O₃ (used as obstructing oxide in charge trap flash memory) with graphene. This article reviews the amalgamation of oxides such as high-κ dielectrics with graphene, which are necessary for the understanding of top-gated electronic devices made by graphene which includes field-effect transistors and other electronic devices.